ANALISIS URGENSI PEMERIKSAAN DIGITAL FORENSIK PADA PERSIDANGAN TINDAK PIDANA INFORMASI DAN TRANSAKSI ELEKTRONIK PERKARA MELANGGAR KESUSILAAN DAN RELEVANSINYA DENGAN PERTIMBANGAN HUKUM HAKIM DALAM MENJATUHKAN PUTUSAN - Lutfi Akmal; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
In handling crime cases with the use of technology information oftenrequires forensics. Forensics is an activity for conduct investigations andestablish facts related to criminal incidents and other legal matters. Forensicanalysis is an important step in computer crime, especially when it comes tobringing it into court.The type of research used is normative juridical research. In this research,the researcher discusses the level of legal synchronization, which aims to revealthe extent to which certain laws are compatible vertically or horizontally.The conclusions that can be obtained from the results of the study areFirst, Digital Forensics Legal Arrangements in the Criminal Evidence System inIndonesia are not specifically regulated in laws and regulations. However, Article5 paragraph (1) of Law Number 11 of 2008 in conjunction with Law Number 19of 2016 concerning Information and Electronic Technology (ITE) contains a formof expansion of evidence outside Article 184 of the Criminal Procedure Code.Where in the law it is recognized that Electronic Information and/or ElectronicDocuments and/or their printouts are legal evidence. Where in article 5paragraph (2) of the Law on Information and Electronic Transactions it isclarified that the evidence referred to in paragraph (1) is an extension of legalevidence in accordance with the applicable procedural law. Second, the Role ofDigital Forensics in Information and Electronic Transaction (ITE) Crime Trialsin Cases Violating Morality and Its Relevance With Judges' Legal Considerationsin Making Decisions, namely in examining digital forensic evidence, applyingprinciples, it is important that the process takes place in accordance with the law.applicable and the basic principles can be applied properly. Digital ForensicClarification is also divided based on the physical.Keywords: Examination, Digital Forensics, Morality, Legal Consideration,Judge.